2011
DOI: 10.1016/j.taap.2011.06.026
|View full text |Cite
|
Sign up to set email alerts
|

2,3,7,8-Tetrachlorodibenzo-p-dioxin-mediated disruption of the CD40 ligand-induced activation of primary human B cells

Abstract: Suppression of the primary antibody response is particularly sensitive to suppression by 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) in mice; however, surprisingly little is known concerning the effects of TCDD on humoral immunity or B cell function in humans. Results from a limited number of previous studies, primarily employing in vitro activation models, suggested that human B cell effector function is suppressed by TCDD. The present study sought to extend these findings by investigating, in primary human B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 45 publications
4
33
0
Order By: Relevance
“…1A and B). The results are in accordance with a previous report showing that TCDD significantly suppresses the number of cells secreting IgM (Lu et al, 2011). The IC 50 from the two endpoints were found to differ over 150-fold.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…1A and B). The results are in accordance with a previous report showing that TCDD significantly suppresses the number of cells secreting IgM (Lu et al, 2011). The IC 50 from the two endpoints were found to differ over 150-fold.…”
Section: Discussionsupporting
confidence: 93%
“…Within the immune system, TCDD has been established to directly alter B-cell function as evidenced by the suppression of humoral immune responses (Crawford et al, 2003;Sulentic et al, 1998). Although much of the current understanding of TCDD-induced B-cell dysfunction has been derived from mouse studies and murine cell lines, recent publications using primary cells have confirmed that TCDD suppresses the activation and differentiation of human B cells (Lu et al, 2010(Lu et al, , 2011Phadnis-Moghe et al, 2015). Furthermore, results from studies using a primary B-cell model indicated that a subset of the human donors did not respond to TCDD suggesting that this model might be valuable in modeling interindividual variability (Lu et al, 2010).…”
mentioning
confidence: 99%
“…TCDD is a ubiquitous environment contaminant, which exhibits a wide spectrum of toxicity including immunotoxicity (51, 52). TCDD has been shown to suppress humoral immunity by disrupting the function of human mature B cells (31, 53, 54). Here the reported impairment of B cell development may represent an additional mechanism of immune suppression by TCDD.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our data indicated that ITE inhibited B cell differentiation into Ig-producing plasma cells. In previous papers, the highly potent AhR agonist TCDD was shown to suppress the production of IgM in human B cells and a lipopolysaccharide (LPS)-induced transformed mouse B cell line, CH12.LX, and to inhibit the differentiation into Igproducing plasma cells (11,12,20,21). More recently, it was reported that benzo[a]pyrene also suppressed the differentiation into plasma cells in human B cells (2).…”
Section: Discussionmentioning
confidence: 99%